Det syriske Adams Testamente - Christensen, Peter; Kristensen, Stefan; Norsker, Amanda; Larsen, Anders; Siegismund, Kasper; Ehrensvärd, Martin; Holst, Søren (Dansk Teologisk Tidsskrift, 2015)
The article presents a Danish translation of the oldest extant manuscript of the Syriac Testament of Adam. This manuscript comprises the two first sections (the Horarium and Prophecy) of the total of three sections usually described as making up this composite text. In addition to giving an introduction and translation, the article discusses key issues of the text’s language and theology and aspects of its interpretation of the Garden of Eden story, such as the nature of the forbidden fruit, the future fate of Adam and its Christological implications.